Genetic and Molecular Analysis of Root Hair Development in Arabis alpina - Mapar, Mona; Chopra, Divykriti; Stephan, Lisa; Schrader, Andrea; Sun, Hequan; Schneeberger, Korbinian; Albani, Maria; Coupland, George; Hülskamp, Martin (Frontiers in Plant Science, 2021)
Root hair formation in Arabidopsis thaliana is a well-established model system for epidermal patterning and morphogenesis in plants. Over the last decades, many underlying regulatory genes and well-established networks have been identified by thorough genetic and molecular analysis. In this study, we used a forward genetic approach to identify genes involved in root hair development in Arabis alpina, a related crucifer species that diverged from A. thaliana approximately 26-40 million years ago. We found all root hair mutant classes known in A. thaliana and identified orthologous regulatory genes by whole genome or candidate gene sequencing. Our findings indicate that the gene-phenotype relationships regulating root hair development are largely conserved between A. thaliana and A. alpina. Concordantly, a detailed analysis of one mutant with multiple hairs originating from one cell suggested that a mutation in the SUPERCENTIPEDE1 (SCN1) gene is causal for the phenotype and that AaSCN1 is fully functional in A. thaliana. Interestingly, we also found differences in the regulation of root hair differentiation and morphogenesis between the species, and a subset of root hair mutants could not be explained by mutations in orthologs of known genes from A. thaliana. This analysis provides insight into the conservation and divergence of root hair regulation in the Brassicaceae.